Evaluation Of Public Knowledge And Clinical Management Of Depression In The State Of Penang, Malaysia - Mehmood Khan, Tahir (2009)
Depression is one of the most important public health issues in Malaysian and global context. Depresi atau kemurungan (depression) merupakan satu daripada isu kesihatan global yang paling penting, begitu juga dalam konteks di Malaysia.